2016
DOI: 10.1111/cbdd.12713
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Novel Inhibitors of the Human Aquaporin‐1 Water Channel

Abstract: Aquaporins (AQPs) are a family of membrane proteins that function as channels facilitating water transport in response to osmotic gradients. These play critical roles in several normal physiological and pathological states and are targets for drug discovery. Selective inhibition of the AQP1 water channel may provide a new approach for the treatment of several disorders including ocular hypertension/glaucoma, congestive heart failure, brain swelling associated with a stroke, corneal and macular edema, pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…The availability of large numbers of synchronized Xenopus eggs and embryos, their simple culture requirements, and their rapid development make them ideal for high‐throughput screening for a number of medically relevant products, such as compounds that interfere with blood/lymphatic vessel growth, cancer‐promoting regulatory pathways, or organogenesis. Pharmacological screens using Xenopus embryos have identified modulators of angiogenesis (Kälin, Bänziger‐Tobler, Detmar, & Brändli, ), heterotaxy (Dush et al, ), and aquaporin1 activity (Patil et al, ). In addition, high‐throughput screens based on egg extracts have been used to identify modulators of the Fanconi anemia DNA damage response pathway (Landais, Sobeck, Stone, LaChapelle, & Hoatlin, ) and inhibitors of the Wnt pathway (Thorne et al, ).…”
Section: Support For Xenopus Training and Meetingsmentioning
confidence: 99%
“…The availability of large numbers of synchronized Xenopus eggs and embryos, their simple culture requirements, and their rapid development make them ideal for high‐throughput screening for a number of medically relevant products, such as compounds that interfere with blood/lymphatic vessel growth, cancer‐promoting regulatory pathways, or organogenesis. Pharmacological screens using Xenopus embryos have identified modulators of angiogenesis (Kälin, Bänziger‐Tobler, Detmar, & Brändli, ), heterotaxy (Dush et al, ), and aquaporin1 activity (Patil et al, ). In addition, high‐throughput screens based on egg extracts have been used to identify modulators of the Fanconi anemia DNA damage response pathway (Landais, Sobeck, Stone, LaChapelle, & Hoatlin, ) and inhibitors of the Wnt pathway (Thorne et al, ).…”
Section: Support For Xenopus Training and Meetingsmentioning
confidence: 99%
“…Aquaporin (AQP) is a group of membrane channel proteins that regulate the permeability of water and other small molecules. Normal expression of AQP in the brain tissues plays an important role for the local water transport [8]. Moreover, as the aquaporins in the central nervous system, AQP is crucial for the maintenance of normal ion concentrations in the brain tissue [9].…”
Section: Introductionmentioning
confidence: 99%
“…Their study included light-scattering measurements on erythrocytes, though interpretation of possible inhibitory effects was confounded by the multiexponential kinetics of the light-scattering data. Very recently, Patil et al (2016) reported compounds 12 and 13 as AQP1 inhibitors in a small screen. Apparent compound activities were quite variable in Xenopus oocyte, erythrocyte ghost, and AQP1 proteoliposome assays.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a variety of approaches, including high-throughput screening and computational chemistry, have yielded compounds with reported AQP1 inhibition or activation activity (Migliati et al, 2009;Mola et al, 2009;Seeliger et al, 2013;Yool et al, 2013;To et al, 2015;Patil et al, 2016), as summarized in Fig. 1 [tributyl-(2,4,5-trichlorophenoxy) …”
Section: Introductionmentioning
confidence: 99%